Stress at work: a case study involving managers of a top nationwide financial organization - Luciano Zille Pereira; Clarissa Daguer Braga; Antônio Luiz Marques (Revista de Ciências da Administração : RCA, 2008)
This paper presents the main results of a research project that aimed at identifying the main stress factors and diagnosing the occupational stress levels experienced by 191 managers in a large nationwide financial organization working at the organization branch located in the city of Belo Horizonte/MG. The research was conducted under descriptive and explicative research models MTEG (Zille, 2005) and lead to results that pointed out unstable work relations, over dimensioned goals, high levels of worker involvement demanded, work force below actual necessities and poor work inter-relationships as the main stress provokers in managers. Results have shown that 150 out of 168 managers (89,10%) were diagnosed as carrying some level of stress, distributed in the following groups: 59 (35,21%) had low to moderated stress levels;69 (40,97%) had high stress levels and 22 (12,92%) had very high stress levels.